Elucidation And Comparison Of Proteome Profiles In Normal, Precancerous And Cervical Cancer Tissues - Kumarasamy, Gaayathri (2023)
The aim of this study was to determine the protein profiles and differentially expressed proteins in the normal cervix, HPV-associated squamous intraepithelial lesion (SIL) which is precancerous and cervical cancer, extracted from formalin-fixed paraffin-embedded (FFPE) tissues.